2022
DOI: 10.1186/s12913-022-08930-2
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of positive and negative electronic word-of-mouth on the SERVQUAL scale during the COVID-19 epidemic - taking a regional teaching hospital in Taiwan as an example

Abstract: Background In recent years, studies have shown that electronic WOM (eWOM) directly reflects consumers’ post-purchase psychological perception and directly affects repurchase behavior. This information is valued by institutions in various fields. Within the scope of the evaluation of service characteristics, medical service is the least visible and most difficult service attribute to evaluate. Service organizations must have high trust attributes. Therefore, an eWOM review significantly influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 76 publications
4
6
0
Order By: Relevance
“…The findings revealed that the average rating was 3.4 for medical centers, 3.27 for regional hospitals, and 3.08 for military hospitals, indicating that military hospitals’ ratings were lower than those of comparable civilian hospitals. However, on the basis of our comprehensive review and search, only Lee et al [ 17 ] have explored both positive and negative eWOM within the context of military health care institutions. Furthermore, their study was confined to a single health care institution, providing somewhat restricted insights into the broader comprehension of eWOM within the hospital sector.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The findings revealed that the average rating was 3.4 for medical centers, 3.27 for regional hospitals, and 3.08 for military hospitals, indicating that military hospitals’ ratings were lower than those of comparable civilian hospitals. However, on the basis of our comprehensive review and search, only Lee et al [ 17 ] have explored both positive and negative eWOM within the context of military health care institutions. Furthermore, their study was confined to a single health care institution, providing somewhat restricted insights into the broader comprehension of eWOM within the hospital sector.…”
Section: Introductionmentioning
confidence: 99%
“…Their focus was primarily on applying the theory of cognitive dissonance, the theory of the strength of weak ties, and the theory of perceived risk, with no cases integrating SERVQUAL theory. In our search within the “Health Care Sciences & Services” field, only Lee et al [ 17 ] studied positive and negative WOM at a regional teaching hospital in Taiwan. They found that during the COVID-19 pandemic, negative reviews exceeded positive ones, with “Assurance” performing the worst in negative eWOM among the 5 determinants of PZB SERVQUAL, followed by “Responsiveness” and “Reliability” [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In an epoch characterized by the amalgamation of technology and societal awareness, the function of social media marketing has gone beyond traditional limitations, manifesting as a dynamic agent that propels significant transformation through cause-driven initiatives (Sengupta & Behera, 2015). Social media platforms have undergone significant transformations, emerging as influential instruments that facilitate interpersonal connections, magnify diverse perspectives, and mobilize collective endeavors (Lee et al, 2022). Consequently, their capacity to mold and influence attitudes, behaviors, and societal outcomes has attracted considerable scholarly interest (Ushakov & Shatila, 2022).…”
Section: Introductionmentioning
confidence: 99%